Computational Identification and Experimental Demonstration of High‐Performance Methane Sorbents. (27th April 2022) - Nath, Karabi; Ahmed, Alauddin; Siegel, Donald J.; Matzger, Adam J.
Abstract: Remarkable methane uptake is demonstrated experimentally in three metal‐organic frameworks (MOFs) identified by computational screening: UTSA‐76, UMCM‐152 and DUT‐23‐Cu. These MOFs outperform the benchmark sorbent, HKUST‐1, both volumetrically and gravimetrically, under a pressure swing of 80 to 5 bar at 298 K. Although high uptake at elevated pressure is critical for achieving this performance, a low density of high‐affinity sites (coordinatively unsaturated metal centers) also contributes to a more complete release of stored gas at low pressure. The identification of these MOFs facilitates the efficient storage of natural gas via adsorption and provides further evidence of the utility of computational screening in identifying overlooked sorbents. Abstract : Promising MOFs were identified computationally and experimentally demonstrate remarkable methane uptake that outperforms known benchmarks both volumetrically and gravimetrically. An advanced set of interatomic potentials that explicitly account for the presence of coordinatively unsaturated sites (CUS) in MOFs were used to identify the high‐capacity MOFs that were previously overlooked due to the limitation of the general interatomic potentials.